Development of Arduino-Based Rotating Wheel as a Physics Learning Media of Circular Motion - Putri, Maharani Ayu Nurdiana; Krisnaningsih, Erina; Sya’roni, Imam; Devianti, Wanda (Jurnal Pendidikan MIPA, 2022)
Learning media was used to explain the theory and minimize misconceptions. 50% of physics teachers in East Java have difficulty creating learning media of circular motion. Therefore, researchers created an innovation learning media and analyze the perception of physics teachers to Arduino-based "Rotating Wheel" learning media (ABRW). This research used R&D design with a 4-D model. The subjects were 24 physics teachers throughout East Java and 35 students’s XII MA Jabal Noer, Sidoarjo. The instruments used the form of teacher and student response questionnaires and material expert validation sheets. The data analysis is the calculation of the average value of validation results. The result from the physics teacher's and student response more than 65.8% and 75% in very positive category and validation more than 85% with a very valid categori. Thus, it was concluded ABRW props are feasible to use as well as learning physics in a circular motion topic. Keywords: arduino, circular motion topic, learning media. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp821-831